Minimally invasive surgical versus transcatheter aortic valve replacement: A multicenter study. (June 2019) - Paparella, Domenico; Santarpino, Giuseppe; Malvindi, Pietro Giorgio; Moscarelli, Marco; Marchese, Alfredo; Guida, Pietro; Carbone, Carmine; Gregorini, Renato; Martinelli, Luigi; Comoglio, Chiara; Coppola, Roberto; Albertini, Alberto; et al.
Abstract: Objectives: Treatment of aortic valve stenosis is evolving, indications for transcatheter approach (TAVI) have increased but also surgical valve replacement has changed with the use of minimally invasive approaches. Comparisons between TAVI and surgery have rarely been done with minimally invasive techniques (mini-SAVR) in the surgical arm. Aim of the present study is to compare mini-SAVR and TAVI in a multicenter recent cohort. Methods: Evaluated were 2904 patients undergone mini-SAVR (2407) or TAVI (497) in 10 different centers in the period 2011–2016. The Heart Team approved treatment for complex cases. The primary outcome is the incidence of 30-day mortality following mini-SAVR and TAVI. Secondary outcomes are the occurrence of major complications following both procedures. Propensity matched comparisons was performed based on multivariable logistic regression model. Results: In the overall population TAVI patients had increased surgical risk (median EuroSCORE II 3.3% vs. 1.7%, p ≤ 0.001) and 30-day mortality was higher (1.5% and 2.8% in mini-SAVR and TAVI respectively, p = 0.048). Propensity score identified 386 patients per group with similar baseline profile (median EuroSCORE II ~3.0%). There was no difference in 30-day mortality (3.4% in mini-SAVR and 2.3% in TAVI; p = 0.396) and stroke, surgical patients had more blood transfusion, kidney dysfunction and required longer ICU and hospital length of stay while TAVI patients had more permanent pace maker insertion. Conclusions: Mini-SAVR and TAVI are both safe and effective to treat aortic stenosis in elderly patients with comorbidities. A joint evaluation by the heart-team is essential to direct patients to the proper approach. Highlights: A comparison between TAVI and minimally invasive techniques has rarely been done In a propensity-matched comparison from 10 different hospitals, TAVI and mini-SAVR provided optimal short-term outcome. 30-day mortality was 3.4% in mini-SAVR and 2.3% in TAVI (p = 0.396) Mini-SAVR and TAVI are both safe and effective to treat aortic stenosis in elderly patients with comorbidities.